Management of Education Curriculum in Improving the Quality of Learning in the 21st Century - Richi Irawan; Riani Watania (Jurnal Pendidikan Vokasi Indonesia, 2022)
The modernization era has had an impact on education in the 21st century marked by the existence of technology behind learning and the use of technology in all fields of learning activities. The influence of technology that continues to develop creates new demands for an industry and employment so that prospective workers are able to meet the needs and qualification standards of ability to use technology. So to make developments in improving the quality of 21st century learning, an application of technology is needed. The quality of learning in the 21st century which is very limited will be more dynamic and not limited by the presence of technology. To develop and improve the quality of learning in the 21st century, it is necessary to adjust and improve the learning curriculum to be able to harmonize and apply and fulfill all the skills needed by students. Changes in the curriculum to improve the quality of learning in the 21st century must be carried out thoroughly, both in the internal and external curriculum. Changes in the education curriculum in improving the quality of learning in the 21st century will help answer all the challenges and difficulties of students in facing the demands of the industrial world in the future.